Ubiquitin C-terminal hydrolase is a novel biomarker in humans for severe traumatic brain injury - Papa, Linda; Akinyi, Linnet; Liu, Ming Cheng; Pineda, Jose A; Tepas, 3rd, Joseph J; Oli, Monika W; Zheng, Wenrong; Robinson, Gillian; Robicsek, Steven A; Gabrielli, Andrea; Heaton, Shelley C; Hannay, H Julia; et al. (Critical care medicine, 2010)
Ubiquitin C-terminal hydrolase (UCH-L1), also called neuronal-specific protein gene product (PGP 9.3), is highly abundant in neurons. To assess the reliability of UCH-L1 as a potential biomarker for traumatic brain injury (TBI) this study compared cerebrospinal fluid (CSF) levels of UCH-L1 from adult patients with severe TBI to uninjured controls; and examined the relationship between levels with severity of injury, complications and functional outcome. This study was designed as prospective case control study. This study enrolled 66 patients, 41 with severe TBI, defined by a Glasgow coma scale (GCS) score of < or =8, who underwent intraventricular intracranial pressure monitoring and 25 controls without TBI requiring CSF drainage for other medical reasons. : Two hospital system level I trauma centers. Ventricular CSF was sampled from each patient at 6, 12, 24, 48, 72, 96, 120, 144, and 168 hrs following TBI and analyzed for UCH-L1. Injury severity was assessed by the GCS score, Marshall Classification on computed tomography and a complicated postinjury course. Mortality was assessed at 6 wks and long-term outcome was assessed using the Glasgow outcome score 6 months after injury. TBI patients had significantly elevated CSF levels of UCH-L1 at each time point after injury compared to uninjured controls. Overall mean levels of UCH-L1 in TBI patients was 44.2 ng/mL (+/-7.9) compared with 2.7 ng/mL (+/-0.7) in controls (p <.001). There were significantly higher levels of UCH-L1 in patients with a lower GCS score at 24 hrs, in those with postinjury complications, in those with 6-wk mortality, and in those with a poor 6-month dichotomized Glasgow outcome score. These data suggest that this novel biomarker has the potential to determine injury severity in TBI patients. Further studies are needed to validate these findings in a larger sample.